2020
DOI: 10.3390/polym12071450
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery System Based on pH-Sensitive Biocompatible Poly(2-vinyl pyridine)-b-poly(ethylene oxide) Nanomicelles Loaded with Curcumin and 5-Fluorouracil

Abstract: Smart polymeric micelles (PMs) are of practical interest as nanocarriers for the encapsulation and controlled release of hydrophobic drugs. Two hydrophobic drugs, naturally-based curcumin (Cur) and synthetic 5-fluorouracil (5-FU), were loaded into the PMs formed by a well-defined pH-sensitive poly(2-vinyl pyridine)-b-poly(ethylene oxide) (P2VP90-b-PEO398) block copolymer. The influence of the drug loading on the micellar sizes was investigated by dynamic light scattering (DLS) and it appears that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 49 publications
0
49
1
Order By: Relevance
“…Atanase and collaborators [ 87 ] synthesized smart polymeric micelles (PMs) based on poly(2-vinyl pyridine)-b-poly(ethylene oxide) block copolymers as nanocarriers for the encapsulation and controlled release of natural and synthetic hydrophobic drugs. Studies have shown that PMs are sensitive to the pH and protect the natural drug (curcumin) against photodegradation.…”
Section: Smart Nanoparticles In Dentistrymentioning
confidence: 99%
“…Atanase and collaborators [ 87 ] synthesized smart polymeric micelles (PMs) based on poly(2-vinyl pyridine)-b-poly(ethylene oxide) block copolymers as nanocarriers for the encapsulation and controlled release of natural and synthetic hydrophobic drugs. Studies have shown that PMs are sensitive to the pH and protect the natural drug (curcumin) against photodegradation.…”
Section: Smart Nanoparticles In Dentistrymentioning
confidence: 99%
“…An ideal drug carrier must be biocompatible, biodegradable, non-toxic, and have the capability to release the loaded active principles at the desired site of action. Until now, a large number of inorganic and organic materials, which have been formulated as liposomes, organic and inorganic nanoparticles, and hydrogels, have been used as promising drug carriers [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. However, there is an increasing interest in using natural biopolymers for the elaboration of different types of drug delivery systems (DDS) due to their abundance in nature and characteristic features, such as sustainability, biocompatibility, and biodegradability [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To improve the bioavailability of fragile and hydrophobic drugs, nanocarriers have been developed to protect the encapsulated drug from enzymatic degradation, provide controlled release, alter their pharmacokinetics, prolong their residence in plasma, and improve their cytoprotective and antioxidant effects [ 12 , 13 ]. The targeted delivery and cellular internalization of curcumin are also improved by its encapsulation in nanoparticles and nanoemulsions [ 14 ].…”
Section: Introductionmentioning
confidence: 99%